Disclosure of cholesterol recognition motifs in transmembrane domains of the human nicotinic acetylcholine receptor - Baier, Carlos J. (2011)
Fil: Baier, Carlos J. Universidad de Buenos Aires, Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Química y Fisicoquímica Biológicas; Argentina